2021
DOI: 10.48162/rev.39.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea on gas and effluent losses, microbial populations, aerobic stability and chemical compositivo of corn (Zea mays L.) silage

Abstract: We evaluated the effects of urea addition on gas and effluent losses, fermentation profile, microbial populations, aerobic stability and chemical composition of corn silages. A completely randomised design with five levels of urea (0, 0.5, 1.0, 1.5, and 2.0% based on dry matter) and five replicates was used. A decreasing linear effect of urea levels on effluent losses in corn silages was observed. In parallel, an increasing linear effect of urea levels on pH, increasing from 3.49 to 4.12 in silages with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Among the additives, urea promoted lower levels of butyric acid (0.91ppm). This result agrees with the studies by Santos et al (2021), who found a lower concentration in corn silage with a higher share of urea (0.29g kg -1 DM) and a higher concentration of butyric acid in silage without urea (0.39g kg -1 DM).…”
Section: Arqsupporting
confidence: 93%
“…Among the additives, urea promoted lower levels of butyric acid (0.91ppm). This result agrees with the studies by Santos et al (2021), who found a lower concentration in corn silage with a higher share of urea (0.29g kg -1 DM) and a higher concentration of butyric acid in silage without urea (0.39g kg -1 DM).…”
Section: Arqsupporting
confidence: 93%
“…Apart from T-2 toxin, none of the listed mycotoxins in table 1 exceeded the maximum permitted limit set by the European Union. Several authors paid attention to the effect of urea addition (Santos et al, 2021;Fiantok, 2020;Kaewpila et al, 2020;Santos et al, 2020;Zamir et al, 2020;Santos et al, 2018;Kang et al, 2018;Kebede et al, 2018), but monitored the changes in nutritional…”
Section: Resultsmentioning
confidence: 99%
“…The literature reports that the use of hydrolytic agents in the chemical treatment of forages, such as anhydrous ammonia, ammonium hydroxide and urea as a source of ammonia, is capable of causing changes in the fibrous fraction of the cell wall, increasing the digestibility of apNDF caused by the solubilisation of part of the hemicellulose and by the expansion of cellulose [24] Thus, there is a reduction in the NDF content, as the hydrogen bonds are broken, and there is an increase in the hydration of the fibre, thus allowing the access of the microorganisms. However, the effect of urea on forage, the efficiency of using urea in silage, depends on factors such as the applied dose and the forage storage time, so the beneficial effects of ammonia use on forage may not be observed [2].…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility to deterioration is a very important factor that determines the quality of silages [ 2 ] and, consequently, the dry matter (DM) intake, digestibility and productive performance and health of the animals. A decrease in the nutritive value of silages because of the leaching of some nutrients has been reported to cause an increase in DM, NDF, ADF and ash [ 2 ]. Growth of spoilage microorganisms leads to decreases in farm profitability, as the DM losses can reach 20% in corn and sorghum silages.…”
Section: Introductionmentioning
confidence: 99%